Investment casting - Beeley, Peter R.; Smart, Robert F. (Institute of Materials, 1995)
1. Introduction -- 2. Tooling -- 3. Pattern Technology -- 4. Investment Materials and Ceramic Shell Manufacture -- 5. Melting and Casting -- 6. Gating and Feeding Investment Castings -- 7. Finishing Investment Castings -- 8. Health, Safety and Environmental Legislation -- 9. Defects and Non-Destructive Testing -- 10. Metallurgical Aspects: Structure Control -- 11. Design for Investment Casting -- 12. Review of Applications. 12.1. Application to Aerospace. 12.2. General Applications of Investment Castings. 12.3. Jewellery Investment Casting. 12.4. Investment Casting in Surgery and Dentistry.
Keywords: Precision casting.; elektronické knihy; electronic books